ANALISIS KADAR KARBOHIDRAT TEPUNG BEBERAPA JENIS SAGU YANG DIKONSUMSI MASYARAKAT MALUKU - Barney Huwae; Pamella Papilaya (Program Studi Pendidikan Biologi FKIP Unpatti, 2014)
Background: Sago is one type of traditional food ingredient Maluku area that has a high carbohydrate content. In Maluku, there are various sago species in their respective habitats and are consumed by the local people. Several types of sago growing in the Maluku region and have a high economic value is Sagu Tuni, Ihur, Molat, Makanaru and Duri Rotan. Method: Measurement of carbohydrate content of some sago type using spectrophotometer to calculate absorbance value and using linear regression formula to calculate carbohydrate content value. Result: Content of carbohydrate flour Sagu Tuni (Metroxylon rumphii) amounted to 89,13%, Sagu Ihur flour (Metroxylon sylvester) equal to 77,4% and Sagu Molat flour (Metroxylon sagus Rottbol) equal to 88,6%. Conclusion: Further research on sago tubing and any potential contained therein is needed, especially sago flour in order to be a perfect product.